Separation of hydridocarbonyltris(triphenylphosphine) rhodium (I)catalyst using solvent resistant nanofiltration membrane - Nur S.A. Razak,; Maizatul S. Shaharun,; Hilmi Mukhtar,; Mohd F. Taha, (Universiti Kebangsaan Malaysia, 2013)
An investigation was conducted into the nanofiltration of rhodium tris(triphenyl-phosphine) [HRh(CO)(PPh3)3] catalyst used in the hydroformylation of olefins. The large size of the catalyst (>400 Da) – relative to other components of the reaction provides the opportunity for a membrane separation based on retention of the catalyst species while permeating the solvent. The compatibility of the solvent-polyimide membrane (STARMEMTM 122 and STARMEMTM 240) combinations was assessed in terms of the membrane stability in solvent plus non-zero solvent flux at 2.0 MPa. The morphology of the membrane was studied by field emission scanning electron microscopy (FESEM). The solvent flux and membrane rejection of HRh(CO)(PPh3)3 was then determined for the catalyst-solvent-membrane combination in a dead-end pressure cell. Good HRh(CO)(PPh3)3 rejection (>0.93) coupled with good solvent fluxes (>72 L/m2h1 at 2.0 MPa) were obtained in one of the systems tested. The effect of pressure and catalyst concentration on the solvent flux and catalyst rejection was conducted. Increasing pressure substantially improved both solvent flux and catalyst rejection, while increasing catalyst concentration was found to be beneficial in terms of substantial increases in catalyst rejection without significantly affecting the solvent flux.